TiO2 /solid state polymer junction for photovoltaic application - Al-Bat’hi, Souad A. M.; Alaei, Iraj (Trans Tech Publications, 2012)
Solid state polymer electrolyte blend of polyethylene oxide, chitosan, ammonium iodide, and iodine crystals has been prepared by solution cast technique. The highest ionic conductivity of the polymer electrolyte was 1.18 × 10−5 S cm−1 at room temperature. Addition of chitosan to the electrolyte has improved its mechanical properties. A photovoltaic junction with configuration ITO/TiO2-solid state polymer blend electrolyte/ITO has been constructed. The open circuit voltage Voc, short circuit current density Jsc, and fill factor FF% obtained from the photovoltaic system under white light illumination of 100W Tungsten lamp are 320-350 mV, 0.59-2.5μAcm-2 and 42%-59% respectively.